2016
DOI: 10.1089/jmf.2015.0045
|View full text |Cite
|
Sign up to set email alerts
|

Soy Isoflavones and Osteoporotic Bone Loss: A Review with an Emphasis on Modulation of Bone Remodeling

Abstract: Osteoporosis is an age-related disorder that affects both women and men, although estrogen deficiency induced by menopause accelerates bone loss in older women. As the demographic shifts to a more aged population, a growing number of men and women will be afflicted with osteoporosis. Since the current drug therapies available have multiple side effects, including increased risk of developing certain types of cancer or complications, a search for potential nonpharmacologic alternative therapies for osteoporosis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
85
1
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 130 publications
(93 citation statements)
references
References 137 publications
(126 reference statements)
2
85
1
5
Order By: Relevance
“…Increased density of bone collagen fibers was observed in the study. 21 Based on the results of the study, the post ovarioectomy group which was given jackfruit seed extract had a higher collagen fiber density compared to the post ovarioectomy group given high calcium milk. This can occur because in the condition of postmenopausal osteoporosis, the body lacks estrogen hormone which is one of the important hormones that play a role in regulating bone formation.…”
Section: Discussionmentioning
confidence: 99%
“…Increased density of bone collagen fibers was observed in the study. 21 Based on the results of the study, the post ovarioectomy group which was given jackfruit seed extract had a higher collagen fiber density compared to the post ovarioectomy group given high calcium milk. This can occur because in the condition of postmenopausal osteoporosis, the body lacks estrogen hormone which is one of the important hormones that play a role in regulating bone formation.…”
Section: Discussionmentioning
confidence: 99%
“…25 For example, genistein and daidzein can prevent osteoporosis by increasing bone mineral content and density and by stimulating the formation of bone tissue. 26 The antioxidant properties of isoflavones are also believed to protect against atherosclerosis, which is characterized by oxidation of the low density lipoprotein component of cholesterol that blocks the blood flow. 27 Isoflavones can further activate estrogen receptors in the vagina, ovum and lacteal gland by mimicking estrogens or functioning as anti-estrogens, 28 and these have been shown to have an antioxidant ability, similar to vitamin E/C.…”
Section: Discussionmentioning
confidence: 99%
“…Tea flavonoids have been suggested to protect against bone loss, but epidemiologic studies have shown mixed results of habitual tea consumption on BMD and fracture risk, and the results from clinical trials are limited (94). There has been increasing interest in whether isoflavones can promote bone health and ameliorate bone loss (95), but studies are conflicting regarding a positive BMD effect (96). There is little support for the use of isoflavone supplements in Western countries due to inconclusive evidence that these compounds improve BMD or decrease fracture risk (97)(98)(99).…”
Section: Macronutrients and Isoflavonesmentioning
confidence: 99%